Religion–State Relations during the Reign of Umar ibn Abd Al-Aziz (717–720 CE): An Ethical State Model in Classical Islamic Politics - Ahmad Siddiq Setiawan; Hasaruddin Hasaruddin; Syamzan Syukur; Nasaruddin Nasaruddin (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study examines the relationship between religion and the state during the reign of Umar ibn Abd al-Aziz (717–720 CE) from the perspective of Islamic political history. It addresses a significant gap in the existing literature, which has predominantly portrayed Umar ibn Abd al-Aziz as an exemplary moral ruler while paying limited attention to the structural relationship between religious and political authority under his administration. Employing a qualitative library-based method, the study adopts intellectual and political historical approaches to analyze classical Islamic sources alongside contemporary scholarship. The analysis focuses on four key dimensions: political legitimacy, the role of religious scholars, administrative reform, and the ethical orientation of the state. The findings reveal that Umar ibn Abd al-Aziz neither separated religion from the state nor instrumentalized religion solely to legitimize political power. Instead, he developed an integrative model in which religion functioned as the normative foundation of governance, while the state operated as an ethical institution responsible for realizing justice, accountability, and public welfare. This study argues that his administration represents an early articulation of the ethical state in classical Islamic political thought. Its novelty lies in reinterpreting Umar ibn Abd al-Aziz's governance as an institutional model of religion–state relations rather than merely an example of personal piety, thereby contributing to a more structural and theoretical understanding of classical Islamic political thought.